Avaliação de cinco cultivares de bananeira em Baraúna/RN - Fernandes, Paula Lidiane de Oliveira (Universidade Federal Rural do Semi-Árido, 2012)
This study aims to evaluate the agronomic performance of five banana cultivars on their development in the city of Baraúna/RN, as well as its quality, post-harvest shelf life and its acceptance by the potential local consumers. The experiment was established in WG Fruticultura Farm, located in the city of Baraúna/RN. In the first experiment, the agronomic aspects of these cultivars, for example: plant growth, production, diseases appearance. Evaluations of plant growth were made to give birth sixty days after planting until 300 days of development, the physiological analyzes were performed at flowering and disease incidence was assessed during three stages of plant development and production characteristics were evaluated at harvest. In the second experiment, the fruits were picked and took to the Laboratory of Irrigated Agriculture of UFERSA/RN where quality evaluations were realized (shell color, external appearance, loss of weight, pulp yield, skin thickness, vigour, soluble solids, acidity, pH, SS / TA ratio, vitamin C, soluble sugars and starch) of the fruits in the harvest day and stored during 12 days (24°± 2ºC e 55% ± 5% RH) and evaluated every three days. It was realized the sensorial analysis of the fruits when they were ripe. It was used the based in randomized blocks, using five treatments (FHIA 18, Catherine Silver, Guaranteed Silver, Tropical and FHIA 01), in four replications, and the useful plot consisted of six useful plants with spacing of three meters between rows and two meters between plants. The schema of subdivided parcels; the data were submitted to the varying analysis and the averages were compared through the Tukey test under 5% of possibility, in order to evaluate the diseases the no parametric statistic and the Friedman test were realized. In the first experiment, it was concluded that Silver Catarina e Tropical cultivars favorable agronomic features; with respect to the production FHIA 18 was superior; FHIA 18, Catarina e a FHIA 01 were superior with respect to the physiological behavior; FHIA 18, a Catarina e a FHIA 01 showed a bigger photosynthetic rate and with respect to the resistance to disease, it was proved according to the description of each one, where it was proved the existence of yellow sigatoka, for the cultivars FHIA 18, Catarina and FHIA 01, the Tropical and Garantida did not show any symptoms of diseases. In the second experiment, it was concluded that the cultivars Silver Catarina, Silver Garantida e Tropical physico-chemical characteristics obtained higher proved to be good to the human intake until 12 days after being harvested, while the cultivars FHIA 18 e FHIA 01 had lifetime to the nine days of storage.Sensorially, the cultivars Catarina and Guaranteed were classified as the favorite ones by the consuming potentials
Evaluation of five banana cultivars de bananeira in Baraúna/RN
Keywords: Musa sp; Growth; Post-harvest; Musa sp. 2. Crescimento. 3. Pós-Colheita; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA